Stem cell therapy in diabetic foot patients: where are we now? (Faculty of Medicine Universitas Indonesia, 2011)
Diabetic foot (DF) occurs as a concomitant illness of diabetes mellitus (DM). DM is one of the main causes of nontraumatic amputation in Germany with severe peripheral arterial disease (PAD) with critical limb ischemia (CLI) being of major concern. Although modern techniques are available surgical vascularisation and percutaneous intervention are limited. This problem leads increasing numbers of limb amputations in patients with diabetes mellitus. The physiological process of angiogenesis, vasculogenes is and arteriogenesis contribute to the growth of collateral vessels in response to obstructive arterial disease causing limb ischemi. In clinical practice the endogenous angiogenic response is often impaired. Therapeutic angiogenesis is an application of biotechnology to stimulate new vessel formation via local administration of pro-angiogenic growth factors in the form of recombinant protein, or gene therapy, or by implantation of progenitor cells or stem cells that will synthe size multiple angiogenic cytokines. This review summarises the endothelial function and dysfunctionin DM, the mechanism of homing, the transplantation method and the status of clinical trials in stem cell field to treat limb ischemia. (Med J Indones 2011; 20:154-60) Keywords: diabetes mellitus, endothelial progenitor cells, peripheral arterial disease, stem cells, therapeutic angiogenesis